Ethnomedicinal survey of traditional antidiabetic plants in Baturraden and Sumbang - Utaminingrum, Wahyu; Nofrianti, Nofrianti; Hartanti, Dwi (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Background: The scientific-based jamu development program enables the development of medicinal plants in the traditional medicine system that eventual-ly can be used in the formal healthcare system. Baturraden and Sumbang are considered as areas with abundant plant biodiversity in Java, where the local community has used those plants for medicinal purposes. Objective: This study is conducted to qualitative and quantitatively record and conserve the knowledge of the Baturraden and Sumbang community on the utilization of plants for treating diabetes mellitus. Method: The data of the plant’s local names, plant organs, methods of prepara-tion, and routes of administration of the herbal preparations used for treating diabetes mellitus were collected through semi-structured interviews with 97 informants. The species use-value (SUV), the relative frequency of citation (RFC), and fidelity level (FL) of each species were calculated accordingly to determine their relative importance and value to the local community. Result: There were 11 plant species from 10 families mentioned. The most commonly used plant organ, preparation method, and administration route were leaves, decoction, and oral, respectively. The most important and valuable plants were including Piper ornatum (SUV = 0.19, RFC = 0.13, FL = 23.09%) and An-drographis paniculata (SUV = 0.09, RFC = 0.07, FL = 42.86%). Conclusion: As the most critical antidiabetic plant in the studied area, the decoction or infusion of Piper ornatum leaves is taken orally 1-2 times a day. However, there are no reports on its anti-diabetic-related activities available to date. In contrast, the uses of Andrographis paniculata as the antidiabetic agent has been widely proven. Baturraden and Sumbang people orally consumed the decoction of this plant’s leaves once a day for the said purpose